Modernization of postgraduate education: contemporary outlook and priorities - Сергеєва, Лариса Миколаївна (Pedagogy of Higher and Secondary Education, 2015)
Serheieva L. N. Modernization of postgraduate education: contemporary outlook and priorities. The article deals with establishing new forms of organizing postgraduate pedagogical education for ensuring the competitive advantage of pedagogical and scientific-pedagogical staff. Innovative approaches to the implementation of new forms of postgraduate pedagogical education are revealed.